2021
DOI: 10.1111/ffe.13470
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and failure characteristics of sandstone subjected to true‐triaxial unloading: An experimental and numerical study

Abstract: In this research, we conducted both laboratory experiments and discrete element simulations to investigate the influence of maximum principal stress level on true‐triaxial unloading behaviors of sandstone samples. The results show that as the level of σ1 at the unloading point increases, the ultimate bearing capacity of sandstone sample is increasingly strengthened, while the sample collapses more easily during the unloading process, and the failure mode of sample changes from mixed tensile‐shear failure to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…While these studies did analyze the failure characteristics of rock samples during the pre-peak hardening stage and post-peak softening stage, they did not specifically account for the influence of rock heterogeneity. Through laboratory experiments and discrete element simulations, Xiao et al [39] observed that as the σ 1 level increases, the failure mode of the specimen transitions from mixed tensile-shear failure to shear failure. Additionally, they found a strong correlation between the formation of large cracks in rock samples and the material heterogeneity and true triaxial stress state.…”
Section: Introductionmentioning
confidence: 99%
“…While these studies did analyze the failure characteristics of rock samples during the pre-peak hardening stage and post-peak softening stage, they did not specifically account for the influence of rock heterogeneity. Through laboratory experiments and discrete element simulations, Xiao et al [39] observed that as the σ 1 level increases, the failure mode of the specimen transitions from mixed tensile-shear failure to shear failure. Additionally, they found a strong correlation between the formation of large cracks in rock samples and the material heterogeneity and true triaxial stress state.…”
Section: Introductionmentioning
confidence: 99%
“…With the increase in the unloading rate, the more severe the failure was, the more the cracks split. Xiao et al (2021) [36] carried out laboratory tests and discrete element simulation to study the mechanical properties of sandstone under the unloading condition of maximum principal stress. The results showed that: with the increase in maximum principal stress, the bearing limit of sandstone could be improved, but it was more likely to be destroyed when unloading.…”
Section: Introductionmentioning
confidence: 99%